2019
DOI: 10.1016/j.maturitas.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental design for dementia care - towards more meaningful experiences through design

Abstract: Highlights  (Systematic) reviews from the fields of assistive technology for dementia care and healing environments research show opportunities for environmental design for dementia care.  Insights from both fields could better inform the designers of dementia care environments.  A multidisciplinary and user-centred design approach might broaden opportunities for more meaningful environmental design for dementia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
(31 reference statements)
0
29
0
2
Order By: Relevance
“…Across a wide range of studies, various types of nature representations have been used (see [11] for a review), varying from real plants or nature elements to images, posters and videos [10,12]. Additionally, nature can also be made accessible via VR or AR, for example as an augmented biking exercise with augmented nature [21][22][23] or virtual nature in nursing homes for recreational purposes [13,24].…”
Section: Digital Nature Representationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across a wide range of studies, various types of nature representations have been used (see [11] for a review), varying from real plants or nature elements to images, posters and videos [10,12]. Additionally, nature can also be made accessible via VR or AR, for example as an augmented biking exercise with augmented nature [21][22][23] or virtual nature in nursing homes for recreational purposes [13,24].…”
Section: Digital Nature Representationsmentioning
confidence: 99%
“…Thus, whereas on the one hand, one could argue that wild nature scenes are more fascinating and could function as conversation starters promoting social interaction (cf. [13]), on the other hand, tended nature scenes such as gardens or parks might be considered more suitable as they are readily associated with social presence and safety.…”
Section: Variety In Nature Types: Tended Versus Wild Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Another study, Herriott (2018), shed new insight on designing hospitals and made recommendations for changing the design approach to user participation in larger architectural projects. Ludden et al (2019) proposed technology-enhanced design interventions in builtenvironments that reduced restlessness behavior and provided meaningful sensory experiences for people with dementia. Jakob & Collier (2017) explored the role of textiles in facilitating multi-sensory enriched environments and meaningful occupation for people living with dementia living in care-homes.…”
Section: Co-designing Public Places and Built Environmentsmentioning
confidence: 99%
“…Chromatic environments can thus induce a positive feeling for users, while becoming stimulating and attractive spaces. 7 The studies identified in the context of this review of the literature make their contribution to the problem of the impact of vision disorders [8][9][10][11] and cognitive pathologies [12][13][14][15][16][17][18][19][20][21][22] on perception and adaptation, by color and light, from the inhabited environment of the dependent elderly person. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] This article aims to identify the factors favorable to the management of addiction and loss of autonomy by adapting the environment of the elderly concerned, through color design and light design.…”
Section: Introductionmentioning
confidence: 99%